Impact of Agricultural Extension Services Access and Cooperative Membership on Farmers’ Welfare: Evidence From Tigray, Northern Ethiopia - TEFERA ALI; HADUSH MUUZ; GEBREHIWOT KIDANEMARIAM; HAILU ALEM; KAHSAY SHISHAY (Zagadnienia Ekonomiki Rolnej, 2025)
This study investigates the effects of agricultural extension services and cooperative membership on smallholder farmers’ welfare in Northern Ethiopia.